THE EFFECT OF GLOBAL ENGLISH ON EFL STUDENTS’ MOTIVATION TO LEARN ENGLISH - Chotimmah, Ammaariyah Khusnul; Linda, Linda; Muntiningsih, Ratna (IJIET (International Journal of Indonesian Education and Teaching), 2023)
This study aims to describe the effect of Global English on the learning motivation of EFL Students in learning English. The researcher used a qualitative descriptive methodology to analyze the data and several previous studies to support the data. Researchers researched EFL Students in the English Education Study Program of one private university in Cirebon. Data were specifically obtained by distributing questionnaires and direct interviews with EFL Students regarding the development of Global English and its effect on the learning motivation of EFL Students. Based on the results of the study, 2 broad categories of motivation affect the development of Global English on their motivation, which are intrinsic motivation and extrinsic motivation. As for the explanation of intrinsic motivation, namely the motivation that comes from EFL Students, that includes improving language skills for all purposes, having a larger scope of learning goals, knowing different types of English, and so on. While the notion of extrinsic motivation is the motivation that comes from outside EFL Students, which includes getting a greater opportunity to contribute to the world community, getting a better type of job, and getting a kind of higher quality education in particular.